Associated factors of professional burnout among faculty members of graduate stricto sensu programs in language teaching and linguistics: a cross-sectional study - Barreto, Maynara Fernanda Carvalho; Galdino, Maria José Quina; Oliveira, Eloiza Rodrigues Vidal de; Fernandes, Frederico Garcia; Martins, Júlia Trevisan; Marziale, Maria Helena Palucci; Marcon, Sonia Silva; Haddad, Maria do Carmo Fernandez Lourenço (São Paulo Medical Journal, 2023)
BACKGROUND: The burnout syndrome can be avoided and/or have its signs and symptoms reduced by knowing the five associated factors that help identify the health and working conditions of the professors of graduate programs. OBJECTIVE: To analyze the factors associated with burnout among faculty members of graduate stricto sensu programs. DESIGN AND SETTING: A cross-sectional study was conducted among 585 faculty members of Graduate Programs in Language Teaching and Linguistics in Brazil. METHODS: Data were collected through an online questionnaire. The outcomes were the dimensions of burnout and its related factors identified through multiple templates of logistic regression. RESULTS: Faculty members with increased chances of emotional exhaustion and depersonalization mentioned the use of medications due to labor activities. The negative influence of pace and intensity of work, thoughts about quitting the program, and having to produce three or more scientific articles were associated with higher chances of emotional exhaustion, while having to achieve nine hours per week in undergraduate programs was related to reduced personal accomplishment. Having a conjugal relationship, satisfaction with health and work, post-doctoral degree, autonomy, and good interpersonal relationships with faculty members of the program reduced the chances of emotional exhaustion. Reduced chances of depersonalization occurred among those who were satisfied with work, had good interpersonal relationships with advisees and faculty members, and received productivity funding. CONCLUSION: Sociodemographic, health, and occupational factors related to the dimensions of burnout were identified.